Selective Production of Phenol-Rich Bio-Oil From Corn Straw Waste by Direct Microwave Pyrolysis Without Extra Catalyst - Zhao, Zhiyue; Jiang, Zhiwei; Xu, Hong; Yan, Kai (Frontiers in Chemistry, 2021)
We report a sustainable strategy to cleanly address biomass waste with high-value utilization. Phenol-rich bio-oil is selectively produced by direct pyrolysis of biomass waste corn straw (CS) without use of any catalyst in a microwave device. The effects of temperature and power on the yield and composition of pyrolysis products are investigated in detail. Under microwave irradiation, a very fast pyrolysis rate and bio-oil yield as high as 46.7 wt.% were obtained, which were competitive with most of the previous results. GC-MS analysis showed that temperature and power (heating rate) had great influences on the yield of bio-oil and the selectivity of phenolic compounds. The optimal selectivity of phenols in bio-oil was 49.4 area% by adjusting the operating parameters. Besides, we have made detailed statistics on the change trend of some components and different phenols in bio-oil and given the law and reason of their change with temperature and power. The in situ formed highly active biochar from CS with high content of potassium (1.34 wt.%) is responsible for the improvement of phenol-rich oils. This study offers a sustainable way to fully utilize biomass waste and promote the achievement of carbon neutrality.